Knockout of BnaX.SGT.a caused significant sinapine reduction in transgene-free rapeseed mutants generated by protoplast-based CRISPR RNP editing - Moss, Oliver; Li, Xueyuan; Wang, Eu Sheng; Kanagarajan, Selvaraju; Guan, Rui; Ivarson, Emelie; Zhu, Li-Hua (Frontiers in Plant Science, 2025)
Rapeseed (Brassica napus L.) is known for its high-quality seed oil and protein content. However, its use in animal feed is restricted due to antinutritional factors present in the seedcake, with sinapine being one of the main compounds that reduces palatability. Attempts to develop rapeseed germplasm with lower sinapine levels through traditional breeding methods have shown limited progress. Genetic transformation methods could create new genotypes with reduced sinapine levels by silencing key genes involved in sinapine biosynthesis, though these methods often result in transgenic or genetically modified plants. The recent development of CRISPR-Cas technology provides a precise and efficient approach to crop improvement, with the potential to generate transgene-free mutants. In this study, we targeted the BnaX.SGT.a genes for knockout using CRISPR-Cas editing. By utilizing our newly established protoplast regeneration and transfection protocol for rapeseed, we demonstrated that DNA-free CRISPR editing via protoplast-based ribonucleoprotein (RNP) delivery was highly effective. We achieved successful knockout of the BnaX.SGT.a paralogues, with an average mutation efficiency of over 30%. Sequencing results revealed a variety of mutation types, from 1 bp insertions to 10 bp deletions, with most mutants exhibiting frameshift mutations that led to premature stop codons. The mutants displayed no visible phenotypic differences in growth patterns or flowering compared to the wild type. Importantly, sinapine content was significantly reduced in all T2 generation mutants analysed, while seed weight remained comparable between mutants and the wild type.